Prediksi Kepribadian Mahasiswa Menggunakan Naïve Bayes - Muhammat Rasid Ridho; Sasa Ani Arnomo; Fifi Fifi; Khisal Khisal; Vina Fariska (LPPM Universitas Putera Batam, 2023)
College students are in a transitional phase from youth to adulthood. The transition period makes students still unstable to control their emotions. It makes his curiosity towards new things increase which then shows his personality traits. The purpose of this study was to find out how researchers collect data about personality from students, to find out how to classify personality from the data that has been collected. Research methods start from collecting data using Text Preprocessing questionnaires, Data Training, Classification, Testing, to making predictions. After applying the classification algorithm with the Naïve Bayes algorithm, the Train Score is 0.947 and the Test Score is 0.879. Trials have also been carried out to make predictions with new data whose results are correct.